Factors affecting tracheostomy in critically ill paediatric patients in Japan: a data-based analysis - Tadashi Ishihara; Hiroshi Tanaka (BMC, 2020)
Abstract Background There has been an increasing number of children surviving with high medical needs, for whom tracheostomy and/or home ventilation is part of their chronic disease management. The purpose of this study was to describe the indications, epidemiology, frequency, and associated factors for tracheostomy in critically ill paediatric patients using the data available in the Japanese Registry of Paediatric Acute Care (JaRPAC). Methods This multicentre epidemiologic study collected data concerning paediatric tracheostomy from the JaRPAC database. Patients were divided into two groups: those with or without tracheostomies when they were discharged from the Intensive Care Unit (ICU) or Paediatric Intensive Care Unit (PICU). Consecutive patients aged ≤16 years who did not undergo tracheostomy when admitted to ICU or PICU between April 2014 and March 2017 were included. Results A total of 23 hospitals participated, involving 6199 paediatric patients registered in the JaRPAC database during the study period. Of the registered paediatric patients, 5769 (95%) patients were admitted to the ICUs or PICUs without tracheostomies. Among the patients, 181 patients (3.1%) had undergone tracheostomies. There were significant differences in chronic conditions (134, 74.0% versus 3096, 55.4%, p <  0.01), chromosomal anomalies (19, 10.5% versus 326, 5.8%, p <  0.01), urgent admission (151, 83.4% versus 3093, 55.4%, p <  0.01). More tracheostomies were performed on patients who were admitted for respiratory failure (61, 33.7% versus 926, 16.1%, p <  0.01) and for post-cardiac pulmonary arrest (CPA) resuscitation (40, 22.1% versus 71, 1.1%, p <  0.01). Conclusions This is the first report to use a large-scale registry of critically ill paediatric patients in Japan to describe the interrelated factors of tracheostomies. Chronic conditions (especially for neuromuscular disease), chromosomal anomaly, admission due to respiratory failure, or treatment for post-CPA resuscitation all had the possibility to be risk factors for tracheostomy.